2014
DOI: 10.1016/j.electacta.2014.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Porous Ni0.5Zn0.5Fe2O4 Nanospheres: Synthesis, Characterization, and Application for Lithium Storage

Abstract: Monodisperse porous Ni0.5Zn0.5Fe2O4 nanospheres have been successfully synthesized by the solvothermal method. The diameter of the nanospheres can be tuned by controlling the reactant concentration. Lower reactant concentration is favoured for the synthesis of mesoporous Ni0.5Zn0.5Fe2O4 nanospheres with higher surface area. The electrochemical results show that mesoporous Ni0.5Zn0.5Fe2O4 nanospheres exhibit high reversible specific capacity (1110 mAh g-1) for Li storage and high capacity retention, with 700 mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 40 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…LiAQC, nr-LiAQC, and nr-LiAQC/G exhibit good charge/discharge performance owing to the introduction of the −CO 2 Li group on AQ that could inhibit the solubility of AQ in organic electrolytes. , Furthermore, the nanorod structure of nr-LiAQC shortens the transport distance of Li ions and electrons and gains rapid insertion/extraction kinetics of lithium ions. , To test the effects of electrochemical properties of the −CO 2 Li group on AQ, we compared with the charge/discharge behavior of AQ in the potential range of 1.0∼4.5 V at a low current density of 20 mA g –1 (0.07 C) (our previous work) . The previous research showed that the first discharge capacity of AQ is up to 215 mAh g –1 .…”
Section: Resultsmentioning
confidence: 99%
“…LiAQC, nr-LiAQC, and nr-LiAQC/G exhibit good charge/discharge performance owing to the introduction of the −CO 2 Li group on AQ that could inhibit the solubility of AQ in organic electrolytes. , Furthermore, the nanorod structure of nr-LiAQC shortens the transport distance of Li ions and electrons and gains rapid insertion/extraction kinetics of lithium ions. , To test the effects of electrochemical properties of the −CO 2 Li group on AQ, we compared with the charge/discharge behavior of AQ in the potential range of 1.0∼4.5 V at a low current density of 20 mA g –1 (0.07 C) (our previous work) . The previous research showed that the first discharge capacity of AQ is up to 215 mAh g –1 .…”
Section: Resultsmentioning
confidence: 99%
“…In literature, nano NZF has been reported for numerous applications such as thin films for microwave heating (Gao et al , 2010), smart multiferroic devices (Guo et al , 2010), microwave absorbers coatings (Yan et al , 2009), biological and biomedical purposes (Al-Qubaisi et al , 2013), semiconductors (Van Uitert, 1956) and lithium storage (Zhang et al , 2014). These applications of NZF are owing to the exhibition of excellent commanded properties such as superparamagnetic behavior, high electrical resistivity, low anisotropy, high capacity retention, high reversible specific capacity and high magnetic permeability (Gao et al , 2010; Guo et al , 2010; Yan et al , 2009; Al-Qubaisi et al , 2013; Van Uitert, 1956; Zhang et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 To circumvent these problems, various approaches have been adopted to improve the electrochemical performance of Fe 3 O 4 , such as element doping and special structure preparation. 4,5 Thus, compounds with partial substitution of Fe in Fe 3 O 4 , such as ZnFe 2 O 4 , 6 NiFe 2 O 4 , 7 and CoFe 2 O 4 , 8 have been suggested as alternative anode materials to Fe 3 O 4 . However, to the best of our knowledge, Fe 3 O 4 based nanostructures with excellent long cycling stability (over 100 cycles) were rarely reported, let alone their high rate performance ($1 A g À1 ).…”
Section: Introductionmentioning
confidence: 99%